Linguistic Features of English Used in Indonesian and Native English Podcasts - Zuhana Syahfitri Siregar; Rusdi Noor Rosa; Rahmadsyah Rangkuti (Journal of General Education and Humanities, 2026)
This study investigates the linguistic features of English used in Indonesian- and English-dominant podcasts through Halliday’s Systemic Functional Linguistics (SFL), focusing on the ideational, interpersonal, and textual metafunctions. The study addresses the limited comparative research on how English is functionally realized across different podcast discourse contexts. The objective of the study is to identify and compare the linguistic features used in Indonesian and English-dominant podcasts and to interpret these differences through the SFL framework. This research employed a qualitative descriptive design using transcript data from six podcast segments selected from Indonesian podcasters (e.g., Deddy Corbuzier, Gita Wirjawan, and Indah G) and English-dominant podcasters (e.g., Joe Rogan, John Mearsheimer, and Kids Rock & Joe). The selected podcast segments discussed similar themes in current affairs and social commentary. The findings suggest that the selected Indonesian podcast data tends to foreground evaluative and affective positioning through stronger modality, rhetorical emphasis, inclusive pronouns, and thematic foregrounding. In contrast, the English-dominant podcast data more frequently demonstrates explanatory reasoning, moderated stance-taking, and linear thematic progression. These differences indicate that English in podcast discourse functions as a flexible communicative resource shaped by sociocultural context, discourse orientation, and audience engagement. The study contributes to discourse analysis, digital media studies, and English language education by demonstrating how English is adapted and functionally organized in multilingual digital communication contexts.